Geotechnics for Natural and Engineered Sustainable Technologies GeoNEst - Krishna, A. Murali; Dey, Arindam; Sreedeep, S.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This contributed volume encompasses contributions by eminent researchers in the field of geotechnical engineering. The chapters of this book are based on the keynote and sub-theme lectures delivered at the Indian Geotechnical Conference 2017. The book provides a comprehensive overview of the current state-of-the-art research and practices in different domains of geotechnical engineering in the areas of soil dynamics, earth retaining structures, ground improvement, and geotechnical and geophysical investigations. It will serve as an ideal resource for academics, researchers, practicing professionals, and students alike. .
Addressing Sustainable Technologies in Geotechnical Engineering -- Interpretation of Natural Ground Properties for Geotechnical Engineering -- Seismic SSI Analysis for Critical Structures -- Recycled Geomaterials for Sustain able Geotechnics -- Displacement Based Static and Seismic Slope Stability Analysis -- Geotechnical Aspects of Analysis and Design of Offshore Wind Turbines -- Modeling and Behavior of Geosynthetic Rein Forced Foundations -- Image Based Characterization Techniques for Geotechnical Applications -- Geotechnical Challenges in Tunelling Through Weak Rocks -- Reliability and Accuracy in Seismic Geophysical investigations -- Elastic-Viscoplastic Models and their Applications in Geotechnical Engineering -- Geotechnical and Geophysical investigation -- Foundations on Difficult Soils -- Slope Stability, Landslides and Natural Disaster Mitigation -- Earth Retaining Structures -- Earth Retaining Structures -- Geoenvironmental Engineering -- Behaviour of Unsaturated Soils -- Geohydrology, Dam and Embankment Engineering -- Rock Mechanics, Tunnelling and Underground Structures -- Ground Improvement Techniques -- Uncertainties, Risk and Reliability in Geotechnical Engineering -- Soil Dynamics and Earthquake Geotechnical Engineering -- Soil Dynamics and Earthquake Geotechnical Engineering -- Transportation Geotechnics -- Sustainable Geotechnics -- Marine Geotechnics -- Computational Geomechanics and Geotechnical Modelling -- Forensic Geotechnical Engineering and Case Studies -- Allied Areas in Geotechnical Engineering -- Geotechnical and Geophysical Investigation -- Slope Stability, Landslides and Natural Disaster Mitigation -- Geosynthetics Engineering. .
Keywords: Engineering geology; Geotechnical engineering; Environmental engineering; Biotechnology; Bioremediation; Geoengineering; Geotechnical Engineering and Applied Earth Sciences; Environmental Engineering/Biotechnology.